Coordination Architectures of Manganese Complexes based on the Liagnd 3‐Pytza or Mixed Ligands [3‐Pytza = 5‐(3‐Pyridyl)tetrazole‐2‐acetato]. Issue 12 (30th September 2014) - Zou, Jian Hua; Tian, He; Wang, Zhong; Li, Fu Song; Zhang, Fei Fei; Zhao, Li Yang; Zhang, Ping; Zhu, Da Liang; Yang, Gao Wen; Li, Qiao Yun
Abstract Reactions of K3‐pytza [K3‐pytza = 5‐(3‐pyridyl) tetrazole‐2‐acetato potassium salt] with MnCl2·4H2O and 4, 4′‐bipy or mixed ligands with 4, 4′‐bipy (4, 4′bipy = 4, 4′‐bipyridine), produced two new coordination compounds, [Mn(3‐pytza)2(H2O)2]·2H2O (1) and [Mn(3‐pytza)2(4, 4′‐bipy)] (2). The two compounds were characterized by elemental analysis, IR spectroscopy and single‐crystal X‐ray diffraction. The X‐ray diffraction analysis reveals that compound 1 displays a 1D polymeric chain structure, whereas compound 2 shows a 2D layer network. The two polymers are self‐assembled to form 3D supramolecular networks by hydrogen bonding interactions. Furthermore, the luminescence of 1 and 2 in the solid state at room temperature were also investigated.